NLO in the large charge sector of the critical O(N) model at large N - Nicola Andrea Dondi; Giacomo Sberveglieri (Journal of High Energy Physics)
Abstract We compute the next-to-leading correction to the scaling dimension of large-charge operators in the 3d critical O(N) model in a double scaling limit in which both N and the operator charge Q are taken to be large. When Q ≫ N our result matches predictions from the conformal superfluid EFT and allows to extract next-to-leading order corrections to the EFT Wilsonian coefficients. At present, our result represents the most precise determination of large-charge operator scaling dimension in weakly-coupled CFTs.